Interactive Math Learning Using Chopsticks in Early Childhood Education - Novitasari; Sholihah, Izzatus; Hanur, Binti Suaidah (JOSAR (Journal of Students Academic Research), 2025)
This study explores the impact of the use chopsticks in learning math interactively towards the development of fine motor skills among kindergarten learners in East Java Indonesia. Focusing on the use of chopsticks, this study was using a qualitative research design of case study. The study involved classroom observation and semi-structured interviews to gather insight into teacher-child interactions. The sample includes four and five-years-old children and their teacher., selected through purposive sampling. The findings emphasize that math learning using chopsticks assist teacher to recognize students’ prior knowledge. This promotes new learning model to support their concentration by linking new ideas to prior knowledge